What are the benefits of cultivating self-compassion in adults with low back pain? A systematic review - Greff Ballejos, Kellen; Calvetti, Prisla Ücker; Schaab, Bruno Luis; Reppold, Caroline Tozzi (Frontiers in Psychology, 2023)
Introduction Low back pain is one of the most prevalent public health problems in the world, generating psychosocial impacts on quality of life and a high demand for medical care. Self-compassion may be beneficial for low back pain control, however, studies in the area are scarce. Therefore, this systematic review aimed to investigate the benefits of self-compassion-related interventions on low back pain and mental health in adults. Methods The review protocol was registered in PROSPERO and the method was performed according to the PRISMA guidelines. Searches were conducted using the keywords “self-compassion” and “low back pain” in Portuguese, English, and Spanish in the following databases: PubMed, LILACS, SciELO, PePSIC, PsycInfo, Embase, Scopus, Web of Science, and Cochrane. Additional searches were also conducted through the references of the included studies. Results Thirty-three articles were identified and analyzed by two independent reviewers using Rayyan. Four of these studies were included. RoB 2 was used to assess the risk of bias of each study. The main findings suggest that self-compassion-related interventions demonstrate benefits in the treatment of low back pain, as well as reduction in pain intensity, psychological stress, and improvement of pain acceptance. Discussion However, these positive data must be analyzed carefully, as only two studies presented a low risk of bias. Despite growing interest in this field, more research self-compassion-related interventions for low back pain are suggested, since biopsychosocial aspects associated with low back pain can impact the outcome of treatment. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier (CRD42022376341).